SOME BIOLOGICAL AND MORPHOMETRIC INDICATORS OF THE RUTILUS LACUSTRIS IN THE UPPER STREAM OF THE SYRDARYA RIVER (Scientific journal of the Fergana State University, 2024)
The article studied the growth rate by year of life, reproductive ability and morphometric indicators of Rutilus lacustris living in the upper reaches of the Syrdarya River. The linear growth over the years of life of a group of Rutilus lacustris individuals of different ages was determined. Based on the growth of the fish, it was found that two-year-old and three-year-old roaches grew together at all ages; in four-year-olds, the growth rate in the third and fourth years decreased sharply, the reason for which is their sexual maturity. The main morphometric indicators of Rutilus lacustris in the Syrdarya River were studied and analyzed for the first time. Based on morphometric indicators, the ratio of individual parts of the fish body was determined, i.e. in what state the general exterior of individuals of the species is. The absolute fertility of female Rutilus lacustris was studied. This indicator is one of the main ones among the reproductive ability of fish in the conditions of a particular reservoir. The article also briefly discusses the history of studying the ichthyofauna of the Syrdarya River by various researchers.